2013
DOI: 10.1186/1471-2164-14-548
|View full text |Cite
|
Sign up to set email alerts
|

De novo characterization of Larix gmelinii (Rupr.) Rupr. transcriptome and analysis of its gene expression induced by jasmonates

Abstract: BackgroundLarix gmelinii is a dominant tree species in China’s boreal forests and plays an important role in the coniferous ecosystem. It is also one of the most economically important tree species in the Chinese timber industry due to excellent water resistance and anti-corrosion of its wood products. Unfortunately, in Northeast China, L. gmelinii often suffers from serious attacks by diseases and insects. The application of exogenous volatile semiochemicals may induce and enhance its resistance against insec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 88 publications
3
18
0
Order By: Relevance
“…Methyl jasmonate and other JAs are also factors regulating the biosynthesis of cell wall building components (Pauwels et al, 2008; Men et al, 2013). This is notably the case for lignin: we have found that the expression of several methyl jasmonate-up-regulated genes peaks simultaneously with the active jasmonates content, namely orthologs of Arabidopsis MetS1, PAL2, C3H, CCoAOMT, HCT, CAD4 , and 4CL2 (Supplementary Table S6).…”
Section: Discussionmentioning
confidence: 99%
“…Methyl jasmonate and other JAs are also factors regulating the biosynthesis of cell wall building components (Pauwels et al, 2008; Men et al, 2013). This is notably the case for lignin: we have found that the expression of several methyl jasmonate-up-regulated genes peaks simultaneously with the active jasmonates content, namely orthologs of Arabidopsis MetS1, PAL2, C3H, CCoAOMT, HCT, CAD4 , and 4CL2 (Supplementary Table S6).…”
Section: Discussionmentioning
confidence: 99%
“…3a). Similarly, PAL gene expression was significantly higher in JA or MeJA treated Larix gmelinii plants than in the control plants (Men et al, 2013), and PAL enzyme activity increased in exogenously ABA-treated tomato leaves (Song et al, 2011). Chalcone-flavanone isomerase (CHI) is involved in the primary stage of flavonoid biosynthesis, and contributes to plant adaptive and protective responses to environmental stress.…”
Section: Effects Of Phytohormone Treatments On the Expressions Of Phementioning
confidence: 99%
“…The dynamic transcriptome response to different exposure durations may vary depending on the nature of the stress. Genes implicated in stress response include enzymes of primary and secondary metabolisms such as • Genes encoding for lipoxygenase (LOX), allene oxide cyclase (AOS) and allene oxide synthase (AOC) were upregulated in insect-attacked, in mechanically wounded and in jasmonate-treated trees (Men, Yan, & Liu, 2013;Ralph et al, 2006). • Resistant trees may exhibit a greater transcriptomic response (more responsive genes) to biotic stress than susceptible trees.…”
Section: Responses To Biotic Factorsmentioning
confidence: 99%
“…For example, Adomas et al (2008) found the number of differentially expressed genes after inoculation with a nonpathogen decreased with the exposure times. • Genes involved in stress response and in secondary metabolism are strongly preferentially expressed in trees under biotic stresses (Adomas et al, 2008;Liu et al, 2013;Men et al, 2013;Ralph et al, 2006). For example , the proportion of differentially expressed genes between uninfected and infected trees with white pine blister rust was higher in resistant (3.4%) than in susceptible trees (2.4%).…”
Section: Responses To Biotic Factorsmentioning
confidence: 99%